Gender-based comparison of factors attributing to varying attitude toward COVID-19 vaccination among general public - Khola Noreen , Kausar Aftab Khan , Kashif Ali ,Sabahat Fatima, Basil Rehman (Journal of Rawalpindi Medical College, 2021)
Objective: The objective of this study is to determine the gender-based differences in factors responsible for hesitancy and acceptance towards-19 the COVID-19 vaccination among the general public residing in different cities of Pakistan. Material and Methods: This cross-sectional comparative study was conducted among the general public residing in different cities of Pakistan. Data was collected from15th April to 30th April 2021. The estimated sample size was found to be 380, convenience sampling was used for data collection. The Chi-square test was applied to find gender-based differences in reasons responsible for refusal and uptake of vaccination. P-value < 0.05 was taken as significant. Data were analyzed by using SPSS version 26.0. Results: Out of the total of 380 participants, 101(27%) were males and 279(73%) were females. Significant motives for vaccine uptake include family and friend recommendations, helping society to get back to normal again (75%), and health care recommendations (30%). Males were more receptive to vaccine uptake (p=0.001). Major factors contributing towards vaccine refusal were a perception that Corona Virus is not harmful (90%), mistrust (89%), reservations about vaccine safety (90%) and efficacy (80%), the opposition of friends and family (55%). Females were more hesitant towards COVID vaccination (p=0.04). One of the major reasons for hesitancy towards vaccination was vaccine-associated misinfodemic disseminated by social media. Conclusion: The study concluded the gender-based differences in factors responsible for hesitancy and acceptance of COVID vaccination among the general public. COVID-19 vaccination awareness campaigns should be launch with a special focus on the issues related to vaccine safety and efficacy, offering reassurance and trust-building, addressing misconceptions, especially in females. Keywords: Vaccine, Hesitancy, COVID-19, Misinfodemic.